Photocatalytic degradation of atrazine by heteropolyoxotungstates. Issue 1 (11th December 2019) - Youssef, Loubna; Younes, Ghassan; Al-Oweini, Rami
ABSTRACT: An elegant and eco-friendly photocatalytic degradation approach for the most commonly used herbicide, Atrazine (ATZ); allowed a selective and partial degradation into atrazine-2-hydroxy (Hydroxyatrazine, HAT), which was the sole obtained metabolite. The effect of tungstosilicates and tungstophosphates as photocatalysts under 60 min UV irradiation at two different wavelengths; 254 and 366 nm; was investigated by measuring the absorbance at 10-min intervals, using 720-UV spectrophotometry. ATZ conversion rate was the highest when irradiating with the higher-energy 254 nm UV light. This resulted into 54% degradation in the presence of the silicon-based α -Keggin dodecatungstosilicate [ α -SiW12 O40 ] 4−, whereas 17% was decomposed in its absence. The nature of the heteroatom as well as the structural type of the studied polyoxometalates had a significant effect on the degradation percentage. Accordingly, 31% of ATZ was only decomposed in presence of the phosphorus-analogue [ α -PW12 O40 ] 4− whereas the cyclic super-lacunary octatetracontatungstooctaphosphate [P8 W48 O184 ] 40 − increased the degradation to 41%.